2020
DOI: 10.1007/s13205-020-02461-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of microbiota in the gut of fish species and water

Abstract: To analyze the intestinal microbiota diversity of several important economic fishes in the Loudi area and its correlation with the microbiota of water environment, the high-throughput sequencing based on the bacteria 16S rRNA was used to analyze the intestinal microbiota diversity in fish intestines and water. The results revealed that half of the OTUs in the water sample could be detected in the fish intestine, the proportion of shared OTUs in the intestines of Hypophthalmichthys molitrix and water samples wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…However, our data revealed that the relative abundance of the main bacterial phyla varied with site, as shown by the high relative abundance of Cyanobacteria and relatively less abundant Firmicutes in most of the samples from site 3 and in some of the samples from site 2, compared to site 1. High relative abundance of Cyanobacteria was previously reported in the microbiota of eggs and larvae of the channel catfish [41] and in juveniles of grass carp (Ctenopharyngodon idella) [41], both freshwater species. Since the broodstock water in sites 2 and 3 had a lower temperature (mean ∼ = 16 • C) and salinity than site 1, environmental conditions including these two factors may explain the higher abundance of Cyanobacteria in these sites.…”
Section: Discussionmentioning
confidence: 78%
“…However, our data revealed that the relative abundance of the main bacterial phyla varied with site, as shown by the high relative abundance of Cyanobacteria and relatively less abundant Firmicutes in most of the samples from site 3 and in some of the samples from site 2, compared to site 1. High relative abundance of Cyanobacteria was previously reported in the microbiota of eggs and larvae of the channel catfish [41] and in juveniles of grass carp (Ctenopharyngodon idella) [41], both freshwater species. Since the broodstock water in sites 2 and 3 had a lower temperature (mean ∼ = 16 • C) and salinity than site 1, environmental conditions including these two factors may explain the higher abundance of Cyanobacteria in these sites.…”
Section: Discussionmentioning
confidence: 78%
“…This might be correlated as the stomach is very close to the mouth and oesophagus in crayfish, hence the uptake and transportation of bacteria from water into the gut can be anticipated for marron. In addition, aquaculture practices include tank culture without water exchange for marron, recirculating aquaculture system for tilapia (Giatsis et al ., 2015), and pond culture for silver carp (Zeng et al ., 2020) are the factors linked to bacterial differences in the water. Nevertheless, the microbial communities in the marron gut and rearing water are very different than the fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria present in the aquatic environment and introduced with food may influence the composition of the gut microbiota in fish [ 68 ].…”
Section: Discussionmentioning
confidence: 99%